Interazioni tra farmaci, droghe ed alimenti - Rivalta, Loris; Melina, Susanna; De Matteis, Eva; Cristofalo, F.; Gratteri, Santo (Mission - Open Access, 2024)
This work aims to introduce and analyze synthetically, the main interactions between drugs, between drugs and molecules with pharmaceutical ingredients, between medicines and food, with an initial reference between pharmaceuticals and foods. The most frequent interactions of these substances in drug addicts’ drug habits will also be indicated, to improve their knowledge, evaluation and comparison, in order to recognise the serious possible consequences.